Analisis Framing Pemberitaan Kematian Presiden Iran di Aljazeera.net dan Alarabiya.net - Palendika Alandira; Yadi Mardiyansyah; Irdan Hildansyah; Rohanda Rohanda (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines to analyze the framing of news coverage regarding the death of Iranian President Ebrahim Raisi in two Middle Eastern online media outlets: Alarabiya.net and Aljazeera.net, using Robert N. Entman's framing model. Specifically, the study explores how each media outlet frames Raisi's death through four framing elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The research employs a descriptive-qualitative method with a literature review and documentation technique, focusing on selected news articles published between May 19–21, 2024. Data were analyzed using Entman’s framing approach and tabulated based on original Arabic terms found in each media's narrative. The results show that Alarabiya.net frames Raisi's death as a consequence of systemic failure, associating Raisi with repression and human rights violations. In contrast, Aljazeera.net presents the event as a national tragedy, portraying Raisi as a martyr and a symbol of Islamic resistance. Both media demonstrate highly ideological narrative constructions, reflecting the geopolitical interests of their respective countries. This study confirms that media are not merely conveyors of information, but ideological actors that shape public perception through selective language, visuals, and fact presentation.